2022
DOI: 10.1002/ajpa.24562
|View full text |Cite
|
Sign up to set email alerts
|

At their own pace: Optimal walking speed in children and adolescents

Abstract: Materials and methods: An experimental study was carried out indoors in a sample of 74 children and adolescents of both sexes, between 7 and 14 years of age. Volunteers walked on a treadmill at six different speeds, and the gross cost of transport (CoT), minimum gross energy cost (minCoT), and optimal locomotion speed (OLS) were determined for each individual. These values were compared with the optimal values for adults, as reported in the literature.Results: Our results show that OLS is similar in boys and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Monitored locomotion trials were carried out in a sample of 74 urban children and adolescents of both sexes, aged 7–14 years, to estimate their optimal locomotion speed, their minimum cost of transport, and their energetic cost of walking (BioE8-CEIC 1815) [3 , 13] . Thus, participants walked on the treadmill during six phases corresponding to six different speeds (2, 3, 4, 5, 6 and, 7 km/h), with each phase lasting 5 min.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitored locomotion trials were carried out in a sample of 74 urban children and adolescents of both sexes, aged 7–14 years, to estimate their optimal locomotion speed, their minimum cost of transport, and their energetic cost of walking (BioE8-CEIC 1815) [3 , 13] . Thus, participants walked on the treadmill during six phases corresponding to six different speeds (2, 3, 4, 5, 6 and, 7 km/h), with each phase lasting 5 min.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…These data are also required to understand the evolutionary ecophysiological constraints of hominin past populations. Some of the raw data recorded in these datasets were analysed in a number of original research articles [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] .…”
Section: Objectivementioning
confidence: 99%
“…When we further took into account different categories (age class, sex, and kinship) of group members, we found that adults and females in foraging groups increase the mothers' foraging trip duration and mobility. The presence of independent children, who can walk on their own and join women's foraging trips, does not restrict women from travelling long distances in a larger range, which provides evidence that even young children can achieve adult-level walking capacity [47]. Crucially, consistent with the previous finding from Jang et al [18], we found that children in foraging groups, but not other adults, are likely to increase the net food returns of the mothers, highlighting the role of children as helpers during women's foraging trips.…”
Section: /11mentioning
confidence: 99%
“…Concerning the BioE8 study (Mateos et al, 2021a), no significant differences were shown in the OLS and the minGross COT among sexes (Table 12, Figure 21 a and b), neither significant differences were appreciated in the breadth of the parabola by sex (F= 0.23; p-value= 0.63) (Table 12 and Figure 23). Non-adult individuals consume more Gross COT while walking at adult optimal locomotion speeds compared with their minGross COT at their non-adult optimal locomotion speed, but not significantly (Table 13).…”
Section: Summary Of the Chapter 3 Resultsmentioning
confidence: 95%
“…*The Gross COT of our study represents the minGross COT . The column % Increase ("% Incremento) indicates the difference between the minGross COT of the nonadult individuals walking at their OLS according to Mateos et al (2021a) and the Gross COT estimated taking into account the OLS of the adult individuals following Wall-scheffler, (2012) and Wall-Scheffler & Myers (2013). There are no significant differences when these values are compared (p-value> 0.05).…”
Section: Ols (Kmmentioning
confidence: 99%